Prejudice and misconceptions about tuberculosis and HIV in rural and urban communities in Ethiopia: a challenge for the TB/HIV control program - Abdisa Alemseged; Shifa Jafar; Tesfaye Markos; Jira Chali; Apers Ludwig; Abebe Gemeda; Deribew Amare; Woldemichael Kifle; Deribie Fetene; Bezabih Mesele; Aseffa Abraham; Colebunders Robert (BMC, 2010)
Abstract Background In Ethiopia, where HIV and tuberculosis (TB) are very common, little is known about the prejudice and misconceptions of rural communities towards People living with HIV/AIDS (PLHA) and TB. Methods We conducted a cross sectional study in Gilgel Gibe Field Research area (GGFRA) in southwest Ethiopia to assess the prejudice and misconceptions of rural and urban communities towards PLHA and TB. The study population consisted of 862 randomly selected adults in GGFRA. Data were collected by trained personnel using a pretested structured questionnaire. To triangulate the findings, 8 focus group discussions among women and men were done. Results Of the 862 selected study participants, 750(87%) accepted to be interviewed. The mean age of the respondents was 31.2 (SD ± 11.0). Of the total interviewed individuals, 58% of them were females. More than half of the respondents did not know the possibility of transmission of HIV from a mother to a child or by breast feeding. For fear of contagion of HIV, most people do not want to eat, drink, and share utensils or clothes with a person living with HIV/AIDS. A higher proportion of females [OR = 1.5, (95% CI: 1.0, 2.2)], non-literate individuals [OR = 2.3, (95%CI: 1.4, 3.6)], rural residents [OR = 3.8, (95%CI: 2.2, 6.6)], and individuals who had poor knowledge of HIV/AIDS [OR = 2.8, (95%CI: 1.8, 2.2)] were more likely to have high prejudice towards PLHA than respectively males, literates, urban residents and individuals with good knowledge. Exposure to cold air was implicated as a major cause of TB. Literates had a much better knowledge about the cause and methods of transmission and prevention of TB than non-literates. More than half of the individuals (56%) had high prejudice towards a patient with TB. A larger proportion of females [OR = 1.3, (95% CI: 1.0, 1.9)] and non-literate individuals [OR = 1.4, (95% CI: 1.1, 2.0)] had high prejudice towards patients with TB than males and literate individuals. Conclusion TB/HIV control programs in collaboration with other partners should invest more in social mobilization and education of the communities to rectify the widespread prejudice and misconceptions.